2017
DOI: 10.2147/dddt.s133042
|View full text |Cite
|
Sign up to set email alerts
|

Humanin rescues cultured rat cortical neurons from NMDA-induced toxicity through the alleviation of mitochondrial dysfunction

Abstract: N-methyl-D-aspartate (NDMA) receptor-mediated excitotoxicity has been implicated in a variety of pathological situations such as Alzheimer’s disease (AD) and Parkinson’s disease. However, no effective treatments for the same have been developed so far. Humanin (HN) is a 24-amino acid peptide originally cloned from the brain of patients with AD and it prevents stress-induced cell death in many cells/tissues. In our previous study, HN was found to effectively rescue rat cortical neurons. It is still not clear wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
20
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 36 publications
2
20
0
1
Order By: Relevance
“…Similar findings have been seen with adult models of stroke and amyotrophic lateral sclerosis (Matsuoka, Hashimoto, Aiso, & Nishimoto, ; Xu, Chua, Gao, Hamdy, & Chua, ). HN's protective properties have also been demonstrated in cell culture using models of hypoxia, toxins, and conditions of oxidative stress (Cui et al, ; Men, Zhang, Yang, & Gao, ; Sreekumar et al, ; Zhao, Wang, Li, Zhao, & Zhang, ). A common theme in these studies is the promotion of cell survival under stressful conditions such as energy deficit and cellular degeneration/apoptosis.…”
Section: Introductionmentioning
confidence: 99%
“…Similar findings have been seen with adult models of stroke and amyotrophic lateral sclerosis (Matsuoka, Hashimoto, Aiso, & Nishimoto, ; Xu, Chua, Gao, Hamdy, & Chua, ). HN's protective properties have also been demonstrated in cell culture using models of hypoxia, toxins, and conditions of oxidative stress (Cui et al, ; Men, Zhang, Yang, & Gao, ; Sreekumar et al, ; Zhao, Wang, Li, Zhao, & Zhang, ). A common theme in these studies is the promotion of cell survival under stressful conditions such as energy deficit and cellular degeneration/apoptosis.…”
Section: Introductionmentioning
confidence: 99%
“…It is well established that reactive oxygen species (ROS), which are mainly generated in the mitochondrial respiratory chain, impair sperm production, motility, membrane, and DNA integrity and also influence sperm capacitation (Christova et al ., ; Henkel et al ., ; Brouwers et al ., ; Aitken et al ., ; Lee et al ., ). Humanin has been reported to prevent ROS accumulating in cardiomyocytes (Blasco et al ., ), cortical neurons (Cui et al ., ), retinal pigment epithelium (Minasyan et al ., ), and rat pancreatic beta cells (Paharkova et al ., ), etc. Pre‐treatment with humanin analog can exert cardiologically protective effects against myocardial ischemia and reperfusion injury in mouse models (Muzumdar et al ., ).…”
Section: Discussionmentioning
confidence: 99%
“…These suggest that the mechanism of HN neuroprotection in rat cortical neuron maybe through antagonism of the NMDA receptor. Nonetheless, there is also a conflicting report showing that HN failed to inhibit intracellular Ca 2+ overload triggered by NMDA [ 23 , 30 ]. The reason for the discrepancy is unclear, but one possibility could be due to different concentrations of HN used between these two studies.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, evidence has revealed that HN has a broader spectrum of neuroprotective activity [ 21 , 22 ]. For example, HN has been shown to rescue neurons from NMDA-induced toxicity [ 23 , 24 ]. However, it remains sketchy that the neuroprotection of HN is mediated by the MAPK signals.…”
Section: Introductionmentioning
confidence: 99%